Pinocchio’s Screen Incarnations: An "All-American Real Boy"? - West, Rebecca (Spunti e Ricerche, 2016)
Carlo Lorenzini’s tale of the puppet has been adapted to the screen numerous times and in many nations, from Italy to France to Japan to the United States. In this essay, I analyze three such adaptations, made in the United States. My goals in concentrating on these films are, first, to delve into the question of book to screen adaptation specifically in terms of the defamiliarizing effects that are created when moving from one temporal and national cultural context to another, and, next, to consider how the decision to use animation, live action, or a combination of these filmic techniques influences the reshaping of the Tuscan tale, as well as how the choice of representing Pinocchio through a human actor, a cartoon, or an animated puppet determines the success with which the "essence" of Pinocchio, who inhabits a space between the inanimate thingness of puppethood and the animate humanness of a boy, is captured. My interest is, therefore, in both contextual and textual aspects of adaptation; that is, in the effects of transnational, translinguistic, and transtemporal translations from book to film, as well as in the specifically filmic techniques employed to give life on the screen to a quite particular literary character.